Pengembangan Media Pembelajaran Interaktif Berbasis Powerpoint Tema 4 (Berbagai Pekerjaan) Kelas IV Sekolah Dasar - Fitri Utami; H.A. Hari Witono; Heri Setiawan (Journal of Science Instruction and Technology, 2021)
This study aims to describe the process of making and developing powerpoint-based learning media and to determine the effectiveness of the product resulting from the development of powerpoint-based learning media. This research method is R&D (Research and Development) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Methods of data collection using questionnaires or questionnaires and documentation. The data analysis technique used is qualitative and quantitative data analysis techniques. The population in this study were all fourth-grade students at SDN 2 Montong Terep. While the sample in this study was 6 students because this study used small groups. The results of the research generally show that the score of the media validator gets a percentage of 85.3% with a very decent category, the material validator score gets a percentage of 87% with a very decent category, and the student response score gets a percentage of 82% with a very decent category.